Balancing Work and Caregiving: A Guide for Employers - Carolyn S. Wilken (EDIS)
FCS-2261, a 3-page fact sheet by Carolyn Wilken, is the fifth in a series on caregiving and aging. In today's workplace, employers need to know how to support employees who are also caregivers. This publication contains helpful suggestions for working with Human Resources and employees to benefit everyone. Includes information on developing an in-house support program. Published by the UF Department of Family, Youth and Community Sciences, November 2006.